Nilai, Hambatan, dan Dampak Sosial dalam Prosesi Perkawinan Adat Sasak di Bayan Kabupaten Lombok Utara - Nizar Hilman, Sukran; Suryanti, Ni Made Novi; Ilyas, Muhammad (Humanis, 2022)
This paper discusses the values, barriers, and social impacts of the Sasak Traditional Marriage Procession in Bayan, North Lombok Regency. Data were collected through observation, interviews, and documentation. The theories used are value theory, cultural theory, and social theory. The research findings are (1) Values ??include: a) mutual cooperation values, b) kinship values, c) solidarity values, d) religious values, e) cultural values, f) spiritual values. (2) The social barriers to implementation the traditional Sasak wedding procession in Bayan, North Lombok include (1) Structural Barriers; which includes (a) differences in social stratification; (b) maintaining the status quo; (c) education level; (d) economic differences (2) Religious Barriers, and (3) Cultural Barriers consisting of (a) vested interests; (b) ethnocentric, (c) cultural differences in society, (d) conventional nature of society. (3) The Social impact of Sasak customary marriage in Bayan consists of (1) assigned status; (2) The existence of new social roles; (3) marginalization, (4) group disorganization; (5) acculturation; (6) decrease in social mobility; (7) cultural colonialization; (8) personality changes.